2017
DOI: 10.1007/s11064-017-2358-x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and Ex vivo Neurotoxic Effects of Efavirenz are Greater than Those of Other Common Antiretrovirals

Abstract: Although antiretroviral (ARV) therapy has reduced the incidence of severe dementia associated with HIV infection, there has been a rise in milder neurocognitive complaints. Data from HIV patients taking ARVs have shown measurable neurocognitive improvements during drug cessation, suggesting a neurotoxic role of the therapy itself. Mechanisms underlying potential ARV neurotoxicity have not been thoroughly investigated, however pathologic oxidative stress and mitochondrial dysfunction have been suspected. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…Additionally, a comparison of these findings to the aforementioned studies that reported OCR alternations suggests that there are multiple mechanisms in which electron transport chain function can be affected by ART. Indeed, no changes in viability were found in cells exposed to selected anti-retroviral drugs through the reductivedependent reagent, CTB (Ciavatta et al 2017). These results suggest the existence of a non-mitochondrial mechanism compensating for the lost mitochondrial reductive capacity.…”
Section: Art Toxicity: Beyond the Bbb And Polymerase Gammamentioning
confidence: 83%
See 2 more Smart Citations
“…Additionally, a comparison of these findings to the aforementioned studies that reported OCR alternations suggests that there are multiple mechanisms in which electron transport chain function can be affected by ART. Indeed, no changes in viability were found in cells exposed to selected anti-retroviral drugs through the reductivedependent reagent, CTB (Ciavatta et al 2017). These results suggest the existence of a non-mitochondrial mechanism compensating for the lost mitochondrial reductive capacity.…”
Section: Art Toxicity: Beyond the Bbb And Polymerase Gammamentioning
confidence: 83%
“…A commonly used research method to estimate electron transport chain function is measuring the oxygen consumption rate (OCR), and we (and others) have shown that ART drug combinations induce alternations of OCR (Apostolova et al 2015a;Cohen et al 2017;Velichkovska et al 2018). An interesting observation also indicates that the inhibition of Complex I and alterations to the electron transport chain function may occur without any changes in the OCR levels (Ciavatta et al 2017). The explanation for this phenomenon was suggested to arise from the activation of Complex II to act as a bypass and substituting for the Complex I electronpumping function.…”
Section: Art Toxicity: Beyond the Bbb And Polymerase Gammamentioning
confidence: 97%
See 1 more Smart Citation
“…In a seminal study 36 toxic effects on MAP-2 expression (biomarker for neurons) were found for abacavir, EFV, etravirine, nevaripine, and atazanavir, whereas darunavir, FTC, tenofovir, and maraviroc were nontoxic; also, doravirine+abacavir+lamivudine strongly increased calcium responses to glutamate (potentially increasing excitotoxicity) and didanosine strongly affected mitochondria. Similarly, EFV strongly decreased neuronal viability, reduced neurites and synapses, and reduced excitability of brain slices while tenofovir was less toxic 37 . Akay et al 2014 38 , compared in vivo and in vitro effects of ARVs; in vivo, cART reduced neuronal and synaptic markers in the CNS of SIV-infected monkeys, while cART in uninfected adult rats reduced MAP2 and upregulated proteins associated with anti-oxidation (NQO-1 and HO-1); in vitro (rat neurons), the HIV protease inhibitors ritonavir and saquinovir, alone or in combination, reduced MAP2, increased ROS, and upregulated NQO-1 and HO-1, implicating oxidative effects in the neurotoxicity of ARVs.…”
Section: Introductionmentioning
confidence: 95%
“…For instance, a neurotoxic effect of efavirenz and its major metabolite Electronic supplementary material The online version of this article (https://doi.org/10.1007/s13365-020-00860-1) contains supplementary material, which is available to authorized users. 8-hydroxy-efavirenz was found in neuronal cultures, affecting dendrites and dendritic processes (Robertson et al 2012;Tovar-y-Romo et al 2012;Ciavatta et al 2017). Moreover, studies have shown a detrimental effect of efavirenz on the bloodbrain barrier and on neuronal action potential thresholds (Bertrand and Toborek 2015;Ciavatta et al 2017).…”
Section: Introductionmentioning
confidence: 99%